The use of big data and the internet of things leadership and organizational culture: The innovative capacity of the Amman Stock Exchange - Khaled Yousef Alshboul (Journal of Project Management)
The aim of this study is to investigate the relationship between big data adoption and Internet of Things adoption and entrepreneurial behavior at Amman Stock Exchange The study focuses on how the ability to innovate mainly mediates this link. The study method uses a quantitative approach that includes conducting a professional survey, conducting a statistical analysis, and testing mediation Key results show that the use of big data improves the ability to innovate largely, and affects employees’ practical leadership capabilities The interaction between Internet adoption and leadership capabilities is influenced by product capabilities, which emphasizes the important role of innovation as a mediator in shaping employee behavior emphasizing Practical results of this study show that Amman Stock Exchange companies strategically use big data and IoT technologies to promote innovation. Shortcomings of the study include the specificity of digital work, the reliance on self-reported data, and the use of static analysis. Subsequent research should expand participants and use more comprehensive methods. Recommendation: Embrace technology with an emphasis on innovation, provide leadership training, and increase knowledge about technology, innovation and human behavior.